Synthesis of novel C4-benzazole naphthalimide derivatives with potent anti-tumor properties against murine melanoma. Issue 2 (15th January 2017) - Lu, Yen-Ta; Chen, Tien-Ling; Chang, Kuo-Song; Chang, Chia-Ming; Wei, Tsai-Yin; Liu, Jen-Wei; Hsiao, Chih-Ang; Shih, Tzenge-Lien
Graphical abstract: Abstract: Novel C4-benzazole naphthalimide derivatives were synthesized and tested in vitro and in vivo as anti-cancer drugs. Among these synthetic molecules, compounds9 and10 exhibited cytotoxicity against murine B16F10 melanoma cells. In addition, the above-mentioned compounds significantly suppressed lung tumor metastasis with no visible sign of toxicity.